Pengembangan Aplikasi Pemantauan Kinerja Guru untuk Peningkatan Kualitas Pembelajaran berbasis Web (Studi Kasus: SDN Mulyorejo 1 Malang) - Muhammad Dio Reyhans; Imam Cholissodin; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Monitoring teacher performance is an activity to ensure the implementation of teacher duties. Monitoring the performance of teachers at SDN Mulyorejo 1 Malang is currently still being carried out by visiting the supervisor, which makes it difficult to monitor the file processing done by the teacher. The large number of teacher files makes it difficult to search for files when a file is needed. Based on these problems an application was made to facilitate supervision activities. This system is built on web-based by applying the waterfall model for its development. The web-based system was chosen because the resulting system can be accessed through various platforms. In the requirement analysis process, there were 5 actors, 113 functional requirements, and 1 non-functional requirement. The design is built using sequence diagrams, class diagrams, conceptual data models (CDM), physical data models (PDM), and pseudocode. The implementation process uses the PHP language with object-based infrastructure and data storage using MySQL. The last process is testing using white-box testing for unit testing, black-box testing to validate each need, and usability testing using the System Usability Scale (SUS) method which in this study obtained a value above 80,3 which means very good.